Mapping the national web: Spaces, cultures and borders of diasporic mobilization in the digital age. (3rd September 2021) - Boichak, Olga; Kumar, Priya
Abstract: National web is a series of interlinked online spaces, generated and visited by users who share a common national identity, language and/or an interest in a particular country. For diasporic communities living outside of their country of origin, national web is an entity that emerges through the production and circulation of culturally significant content and genres. A wealth of textual and visual data, produced in the process of mediated communication among diasporic actors, turn social media into a point of entry for mapping national webs. In this paper, we explore hyperlinking behaviours among Ukrainian Canadians to map geographic, linguistic and geopolitical boundaries of the Ukrainian national web. Shining light on the spaces and cultures of diasporic mobilization in the digital age, we identify distinct web spheres that mediate the Ukrainian Canadians' relationship to their country of origin, demonstrating their elevated significance in the current geopolitical context.